Sukzession arktischer Hartboden Lebensgemeinschaften - Streicher, Michael (2014)
Exposed to the low temperatures of high latitudes Thorson’s rule suggests a reduced speed of development in marine invertebrates. This raises the question how the development and succession of assemblages of respective species in the arctic is affected. The duration and chronology of succession, as well as the influence of environmental impacts on arctic benthic assemblages, is not fully understood, especially concerning long-term studies. By analysing species abundances and substrate coverage over an exposure time of one decade the following hypotheses are tested: (i) Exposition time significantly modifies the structure of arctic benthic hard-bottom assemblages, (ii) the macroscopic structure of the substrate surface has a significant influence on the structure of benthic hard-bottom assemblages, and (iii) the succession of benthic hard-bottom assemblages in the Arctic is in general slower compared to the benthic succession in all non-polar climatic zones. In 2002 forty Polyethylene growth panels were installed in about 20 m water depth on an underwater cliff in Kongsfjorden (Svalbard, Norway). Six of these were grooved to create structural diversity on the panel surface. Once a year the ripening epibenthic assemblages were photographed by scientific divers. Until 2007 about eight panels were sampled and replaced annually, thus creating starting points for succession in different years. Additionally a ground truthing was carried out for reference. The findings of this study show a resilience time exceeding a decade. Further the sampling year, age group and exposition time have a notable influence on the different successional stages. The structural diversity of the substrate in contrast showed no significant influence. Lastly the results are discussed in comparison with results of related studies from this and other regions to demonstrate the comparable slow succession.